Investigation into the effect of formulation on intravenous lipid emulsion metabolism using a novel in vitro fluorescent assay - Dougall, Paul W.R. (2016)
Intravenous lipid emulsions are used ubiquitously through the medical field as a source of parenteral nutrition. Development of new formulations requires an understanding of the metabolism of the product. Current methods of rate determination and of metabolism analysis have several drawbacks. Radioactive labelled assays have lower biological relevance, are time consuming due to separation steps and require long substrate preparation. Existing fluorescence assays based around triglyceride hydrolysis are impractical in emulsion systems due to high signal-noise ratio as well as the use of non-specific fluorescent dyes. Colorimetric methods such as the non-esterified fatty acids (NEFA) assay is expensive, requires multiple steps and specialised machinery. Due to the limitations of these techniques we developed a novel fluorescent assay using a lipoprotein lipase specific substrate incorporated into lipid emulsions. The lipoprotein lipase substrate, EnzChek® Lipase Substrate, green fluorescent, 505/515, is based on a triglyceride structure with a fluorescent dye at the Sn1 position and a dark quencher at the Sn2 position. LPL cleaves preferentially at the Sn1 position of triglycerides, which separates the dye from the quencher creating a fluorescent signal. The signal can then be detected using a fluorescent plate reader. Both lipid emulsion particles and EnzChek are substrates for LPL, so the hydrolysis of EnzChek is analogous for native emulsions particles. Over time, in the presence of LPL, fluorescent signal increases as more EnzChek is hydrolysed in tandem with emulsion particles. We have designed a range of emulsions with varied oil and surfactant composition. Using the EnzChek emulsion assay detailed above we are able to follow the rate of metabolism in real-time. This assay has been tested and found to be robust and reproducible. It is able to investigate differences in metabolism between Soybean oil, medium-chain triglyceride and fish oil emulsions. As well as changes in surfactant type and concentration.